Advertisements
Advertisements
Question
It \[\tan^{- 1} \frac{x + 1}{x - 1} + \tan^{- 1} \frac{x - 1}{x} = \tan^{- 1}\] (−7), then the value of x is
Options
0
−2
1
2
Solution
(d) 2
We know that
\[\tan^{- 1} x + \tan^{- 1} y = \tan^{- 1} \left( \frac{x + y}{1 - xy} \right)\]
\[\therefore \tan^{- 1} \left( \frac{x + 1}{x - 1} \right) + \tan^{- 1} \left( \frac{x - 1}{x} \right) = \tan^{- 1} \left( - 7 \right)\]
\[ \Rightarrow \tan^{- 1} \left( \frac{\frac{x + 1}{x - 1} + \frac{x - 1}{x}}{1 - \frac{x + 1}{x - 1} \times \frac{x - 1}{x}} \right) = \tan^{- 1} \left( - 7 \right)\]
\[ \Rightarrow \tan^{- 1} \left( \frac{\frac{x^2 + x + x^2 - 2x + 1}{x\left( x - 1 \right)}}{\frac{x^2 - x - x^2 + 1}{x\left( x - 1 \right)}} \right) = \tan^{- 1} \left( - 7 \right)\]
\[ \Rightarrow \tan^{- 1} \left( \frac{2 x^2 - x + 1}{- x + 1} \right) = \tan^{- 1} \left( - 7 \right)\]
So, we get
\[\frac{2 x^2 - x + 1}{- x + 1} = - 7\]
\[ \Rightarrow 2 x^2 - x + 1 = 7x - 7\]
\[ \Rightarrow 2 x^2 - 8x + 8 = 0\]
\[ \Rightarrow x^2 - 4x + 4 = 0\]
\[ \Rightarrow \left( x - 2 \right)^2 = 0\]
\[ \Rightarrow x = 2\]
APPEARS IN
RELATED QUESTIONS
Solve the equation for x:sin−1x+sin−1(1−x)=cos−1x
Prove that :
`2 tan^-1 (sqrt((a-b)/(a+b))tan(x/2))=cos^-1 ((a cos x+b)/(a+b cosx))`
`sin^-1(sin pi/6)`
`sin^-1(sin (17pi)/8)`
Evaluate the following:
`cos^-1{cos (13pi)/6}`
Evaluate the following:
`sec^-1(sec (2pi)/3)`
Evaluate the following:
`cosec^-1(cosec (11pi)/6)`
Evaluate the following:
`cot^-1(cot (19pi)/6)`
Write the following in the simplest form:
`tan^-1sqrt((a-x)/(a+x)),-a<x<a`
Evaluate the following:
`sin(cos^-1 5/13)`
Prove the following result
`tan(cos^-1 4/5+tan^-1 2/3)=17/6`
Prove the following result
`sin(cos^-1 3/5+sin^-1 5/13)=63/65`
Evaluate:
`tan{cos^-1(-7/25)}`
Evaluate:
`cos(tan^-1 3/4)`
Evaluate:
`sin(tan^-1x+tan^-1 1/x)` for x < 0
If `cos^-1x + cos^-1y =pi/4,` find the value of `sin^-1x+sin^-1y`
If `sin^-1x+sin^-1y=pi/3` and `cos^-1x-cos^-1y=pi/6`, find the values of x and y.
`sin^-1x=pi/6+cos^-1x`
`5tan^-1x+3cot^-1x=2x`
Prove the following result:
`tan^-1 1/4+tan^-1 2/9=sin^-1 1/sqrt5`
Find the value of `tan^-1 (x/y)-tan^-1((x-y)/(x+y))`
Solve the following equation for x:
`tan^-1(2+x)+tan^-1(2-x)=tan^-1 2/3, where x< -sqrt3 or, x>sqrt3`
Solve the following:
`cos^-1x+sin^-1 x/2=π/6`
If `cos^-1 x/2+cos^-1 y/3=alpha,` then prove that `9x^2-12xy cosa+4y^2=36sin^2a.`
`4tan^-1 1/5-tan^-1 1/239=pi/4`
If `sin^-1 (2a)/(1+a^2)-cos^-1 (1-b^2)/(1+b^2)=tan^-1 (2x)/(1-x^2)`, then prove that `x=(a-b)/(1+ab)`
Write the value of tan−1 x + tan−1 `(1/x)` for x < 0.
Write the value of cos−1 (cos 1540°).
Write the value ofWrite the value of \[2 \sin^{- 1} \frac{1}{2} + \cos^{- 1} \left( - \frac{1}{2} \right)\]
Write the value of \[\sin^{- 1} \left( \frac{1}{3} \right) - \cos^{- 1} \left( - \frac{1}{3} \right)\]
Write the principal value of \[\tan^{- 1} 1 + \cos^{- 1} \left( - \frac{1}{2} \right)\]
Write the value of \[\sin^{- 1} \left( \sin\frac{3\pi}{5} \right)\]
If \[\cos\left( \tan^{- 1} x + \cot^{- 1} \sqrt{3} \right) = 0\] , find the value of x.
If \[\cos\left( \sin^{- 1} \frac{2}{5} + \cos^{- 1} x \right) = 0\], find the value of x.
The number of real solutions of the equation \[\sqrt{1 + \cos 2x} = \sqrt{2} \sin^{- 1} (\sin x), - \pi \leq x \leq \pi\]
In a ∆ ABC, if C is a right angle, then
\[\tan^{- 1} \left( \frac{a}{b + c} \right) + \tan^{- 1} \left( \frac{b}{c + a} \right) =\]
If \[\sin^{- 1} \left( \frac{2a}{1 - a^2} \right) + \cos^{- 1} \left( \frac{1 - a^2}{1 + a^2} \right) = \tan^{- 1} \left( \frac{2x}{1 - x^2} \right),\text{ where }a, x \in \left( 0, 1 \right)\] , then, the value of x is
The value of \[\tan\left( \cos^{- 1} \frac{3}{5} + \tan^{- 1} \frac{1}{4} \right)\]
If \[\tan^{- 1} \left( \frac{1}{1 + 1 . 2} \right) + \tan^{- 1} \left( \frac{1}{1 + 2 . 3} \right) + . . . + \tan^{- 1} \left( \frac{1}{1 + n . \left( n + 1 \right)} \right) = \tan^{- 1} \theta\] , then find the value of θ.
Find the domain of `sec^(-1)(3x-1)`.